impact of global warming on plant diseases and insect vectors in Sweden - Roos, Jonas; Hopkins, Richard; Kvarnheden, Anders; Dixelius, Christina (European journal of plant pathology, 2011)
Cold winters and geographic isolation have hitherto protected the Nordic countries from many plant pathogens and insect pests, leading to a comparatively low input of pesticides. The changing climate is projected to lead to a greater rise in temperature in this region, compared to the global mean. In Scandinavia, a milder and more humid climate implies extended growing seasons and possibilities to introduce new crops, but also opportunities for crop pests and pathogens to thrive in the absence of long cold periods. Increased temperatures, changed precipitation patterns and new cultivation practices may lead to a dramatic change in crop health. Examples of diseases and insect pest problems predicted to increase in incidence and severity due to global warming are discussed.